Ответы и объяснения

  • Участник Знаний
2013-03-11T09:36:54+04:00

|-48|/12-(-3)*4     модуль дает положительное число

 

12-(-3)*4  - это знаменатель ?  

тогда

|-48|/12-(-3)*4 = 48 /  (12-(-12)) =48 / (12+12)=48 / 24 =2

 

 

12  - это знаменатель ?  

тогда

|-48|/12  -(-3)*4 = 48/12 -(-12) = 4 +12 = 16

2013-03-11T12:08:03+04:00

|-48|/12-(-3)*4 модуль дает положительное число



12-(-3)*4 - это знаменатель ?

тогда

|-48|/12-(-3)*4 = 48 / (12-(-12)) =48 / (12+12)=48 / 24 =2

12 - это знаменатель ?

тогда

|-48|/12 -(-3)*4 = 48/12 -(-12) = 4 +12 = 16